Transport infrastructure for MED11 countries - Robin Carruthers (Center for Social and Economic Research (CASE), 2012)
Lack of adequate infrastructure is a significant inhibitor to increased trade of the countries of the Mediterranean region. Bringing their transport infrastructure to standards comparable with countries of a similar per capita GDP will be costly but worthwhile. We compare the current quantities of six types of transport infrastructure with international, and estimate the additional quantities needed to reach the benchmarks. We also estimate the cost of that infrastructure and express it as a percentage of GDP. Finally we make tentative estimates of how much trade might be generated and how this might impact on GDP. All the estimates are made for each MED11 country and for each of four scenarios. The highest need for additional infrastructure will be for airport passenger terminals (between 52% and 56%), whereas the lowest need was for more unpaved roads (between 7% and 13%). The investment (including maintenance) cost would be between 0.9% of GDP and 2.4% of GDP, although the investments in some countries would be between 1.4% and 4.5% of GDP. The impact on non-oil international trade would be substantial, but with differences between imports and exports. The overall trade balance of the MED11 region would be an improvement of between 5.4% and 17.2%, although some countries would continue to have a negative balance. A final assessment was of the benefit ratio between the increase in GDP and the cost of transport investment. This varied between about 3 and 8, an indication of the high return to be expected from increased investment in transport infrastructure.
Keywords: F15; O18; O24; R42; 330; Infrastructure; Region; Investment; GDP; Trade; Benefit ratio; Verkehrsinfrastruktur; Verkehrspolitik; Verkehrsinvestition; Makroökonomischer Einfluss; Szenariotechnik; Kosten-Nutzen-Analyse; Mittelmeerraum; Mittlerer Osten; Nordafrika